Morphological description and illustration of the female developmental stages of Stictococcus vayssierei (Homoptera: Stictoccocidae) - Tindo, M.; Doumtsop, A.; Goergen, Georg E.; Hanna, R. (Springer, 2006)
The African root and tuber scale Stictococcus vayssierei Richard is the only known hypogeal species of the family Stictococcidae. Its wide range of host plants together with concurrently field observed differences in host preference provided evidence of polyphagy or the involvement of more than a single-scale species. To establish the baseline information for future taxonomic studies, newly emerged larvae were collected from infested cassava from three sites in the humid forest zone of southern Cameroon. A glass binocular magnifier was used to observe morphological changes of live individuals and slide-mounted individuals of all developmental stages were examined with a compound microscope. Stictococcus vayssierei females went through three developmental stages—two larval instars and an adult stage. The first and second instars were purple-red, while the adult was brown. Body size and the degree of sclerotization of the dorsal line increased in each developmental stage. White waxy secretions on the basal periphery of the second instar, and both dorsum and periphery of the adults, distinguished them from the first instar, which lacks the white waxy secretions. On slide-mounted specimens, certain aspects of the anal complex (i.e. number of opercular plates and -setae) were found to be the most discriminating features of S. vayssierei life stages. These results are useful for further studies on the diversity of subterranean stictoccocid scales.